KEANEKARAGAMAN MESOFAUNA TANAH DAERAH PERTANIAN APEL DESA TULUNGREJO KECAMATAN BUMIAJI KOTA BATU SEBAGAI BIOINDIKATOR - Ibrahim, Hasan; Hudha, Atok Miftachul; Rahardjanto, Abdulkadir (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
The Mesofauna’s soil is a soil fauna which has a body size of 100 µm-< 2 mm its population has been rare because of applying an intensive agriculture system, which is based on the chemical equipment, such as chemical synthetic of fertilizer and synthetic insecticide. Other problem is less information about the diversity of soil mesofauna, especially in the agriculture apples at Tulungrejo, Bumiaji, Batu. The aim of this research is to determine of the species of soil mesofauna, ecology parameter, index of diversity, evenness index and soil fertility in the research area. The research used descriptive quantitative research. Descriptive research aims to describe an event and the events that occurred, quantitative research aims to explain numbers of data analysis using statistical. The research carried in the morning with the plot method (squares). Data were collected by direct observation of the population investigated. The results showed that soil mesofauna were found to consist of a kind Ascocyrtus sp, Homidia cingula, Isotomurus palustris, Pseudacorutes javanicus, Pseudisotoma sensibilis, Sphyroteca dawydoffi, and Macrocheles robustulus. Soil mesofauna of ecology parameters are: (1) density ranged from 0,592 ind/m2–131,556 ind/m2, relative density between of 0,002–0,484. The highest density species Homidia cingula and the lowest is Isotomurus palustris (2) frequency ranged between 0,037–0,926 the relative frequency ranged from 0,012–0,344 with the highest frequency value species Pseudisotoma and the lowest is Isotomurus palustris (3) the highest importance index value species Homidia cingula 0,756, and lowest is Isotomurus palustris 0,013. The index of diversity value Shannon wiener (H’) 1,368 or categories is low diversity values, so the soil fertility degree in the area of the research is low. Evenness value (E) is 0,85, means the population prone to average (E approaching 1). Keywords: Diversity ,Soil mesofauna, Bioindicator, Agriculture of apple